Taiwan's space future: the impact of technological autonomy and international cooperation - Kuan, Yu Lin (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines Taiwan's space technology development and its impact on international standing amidst the tension between the national and global approaches. As Taiwan pursues technological independence, it also engages in international cooperation, thus creating a dilemma between political demands and global ethical expectations. Realist theory posits that technological autonomy and national security enhance a country's global status. In contrast, liberalism emphasizes the need for international cooperation and shared technology in space as a collective human interest. The article puts forward two hypotheses: first, increased international cooperation in the space sector raises Taiwan's influence; second, greater technological autonomy may reduce this influence. This study takes "technological autonomy" and "international cooperation" as independent variables, while "international influence" is the dependent variable. This article surveys Taiwan's space technology decisions and their implications for its international position. It indicates that international collaboration is imperative in expanding Taiwan's impact, whereas an emphasis on independence alone may limit its global reach.